2016
DOI: 10.1097/psy.0000000000000316
|View full text |Cite
|
Sign up to set email alerts
|

Pilot Randomized Study of a Gratitude Journaling Intervention on Heart Rate Variability and Inflammatory Biomarkers in Patients With Stage B Heart Failure

Abstract: Objective Stage B, asymptomatic heart failure (HF) presents a therapeutic window for attenuating disease progression and development of HF symptoms, and improving quality of life. Gratitude, the practice of appreciating positive life features, is highly related to quality of life, leading to development of promising clinical interventions. However, few gratitude studies have investigated objective measures of physical health; most relied on self-report measures. We conducted a pilot study in Stage B HF patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
66
1
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(75 citation statements)
references
References 54 publications
1
66
1
2
Order By: Relevance
“…A similar intervention in HIV patients showed improvements in some health indicators (e.g., antidepressant use) but not in health behaviours or viral load (Moskowitz et al, 2017). Finally, relative to treatment as usual, a gratitude journaling intervention in a sample of 70 asymptomatic heart failure patients improved parasympathetic heart rate variability and reduced inflammation (Redwine et al, 2016). Finally, relative to treatment as usual, a gratitude journaling intervention in a sample of 70 asymptomatic heart failure patients improved parasympathetic heart rate variability and reduced inflammation (Redwine et al, 2016).…”
mentioning
confidence: 93%
See 1 more Smart Citation
“…A similar intervention in HIV patients showed improvements in some health indicators (e.g., antidepressant use) but not in health behaviours or viral load (Moskowitz et al, 2017). Finally, relative to treatment as usual, a gratitude journaling intervention in a sample of 70 asymptomatic heart failure patients improved parasympathetic heart rate variability and reduced inflammation (Redwine et al, 2016). Finally, relative to treatment as usual, a gratitude journaling intervention in a sample of 70 asymptomatic heart failure patients improved parasympathetic heart rate variability and reduced inflammation (Redwine et al, 2016).…”
mentioning
confidence: 93%
“…Another PPI for 67 cancer patients (based on practising optimistic thinking and writing gratitude letters) demonstrated improvements in psychological adaptation to cancer in comparison to an active control condition (Otto, Szczesny, Soriano, Laurenceau, & Siegel, 2016). Finally, relative to treatment as usual, a gratitude journaling intervention in a sample of 70 asymptomatic heart failure patients improved parasympathetic heart rate variability and reduced inflammation (Redwine et al, 2016). Despite their ease of use and acceptability, 15 years has seen fewer than 10 trials of gratitude-based interventions in patients with chronic health conditions.…”
mentioning
confidence: 95%
“…Some studies have reported that gratitude exercises were associated with increases in trait gratitude (R. Emmons & McCullough, 2003; Froh, Sefick, & Emmons, 2008; Rao & Kemper, 2017; Redwine et al, 2016) while other studies have reported no change in trait gratitude as the result of gratitude practices (Harbaugh & Vasey, 2014; Killen & Macaskill, 2015; Krentzman et al, 2015; Toepfer, Cichy, & Peters, 2012). Could trait gratitude increase with the onset of addiction recovery, in the absence of gratitude exercises?…”
Section: 0 Introductionmentioning
confidence: 99%
“…In a recent randomized controlled trial, healthy adults instructed to perform prosocial acts previously linked to increases in eudaimonic well‐being exhibited decreased CTRA gene expression compared to those in the control condition (Nelson‐Coffey, Fritz, Lyubomirsky, & Cole, ). In a small pilot study of patients with heart failure, those assigned to write gratitude journals showed greater reductions in inflammation relative to a treatment‐as‐usual control (Redwine et al, ), though effects of gratitude writing on inflammation are not uniform (Moieni et al, ). Further, a study conducted with adolescents found that volunteering led to decreases in the pro‐inflammatory cytokine IL‐6 as well as positive changes in other cardiovascular risk factors (Schreier, Schonert‐Reichl, & Chen, ).…”
Section: Positive Psychological States and The Neuro‐immune Networkmentioning
confidence: 99%